ANALISIS LUAS LAHAN MINIMUM UNTUK MEMENUHI KEBUTUHAN PETANI PADI SAWAH DI DESA BERASAN MULYA KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
Analysis of Minimum Land Area to Meet the Needs of Wet-Rice Farmers in Beras Mulya Village, Buay Madang Timur District, East OKU Regency. This research was conducted in Berasan Mulya Village, Buay Madang Timur District, East OKU Regency. The method used in this research is survey method. The sampling method used is Disproportionated Stratified Random Sampling. The number of samples taken as many as 30 rice farmers. The results of this study indicate that (1) rice farmer income with land area of 0.25 Ha of Rp. Rp. 3.852.750 / mt, farmers with land area 0.50 Ha earn revenue of Rp. 7,398,220 / mt, farmers with a land area of 0.75 ha earn income of Rp. 13,037,100 / mt, farmers with a land area of 1 ha earn income of Rp. 16.791.050 / mt, farmers with a land area of 1.25 Ha earn income of Rp. 21.247.000 / mt, farmers with a land area of 1.50 ha earn income of Rp.25.525.250 / mt, farmers with a land area of 1.75 ha earn revenue of Rp. 29.366.800 / mt, and farmers with land area of 2 Ha earn income of Rp. 32.385.000 / mt. (2) expenditure of farmers with land area of 0.25 Ha of Rp. 9.559.000 / mt, the expenditure of farmers who have a land area of 0.50 Ha of Rp. 12.375.000 / mt, the expenditure of farmers who have a land area of 0.75 Ha of Rp. 14.578.000 / mt, the expenditure of farmers who have a land area of 1 Ha of Rp.16.290.000 / mt, the expenditure of farmers who have a land area of 1.25 Ha of Rp. 20,703,500 / mt, the expenditure of farmers who have a land area of 1.50 Ha of Rp. 20.699.000 / mt, the expenditure of farmers who have a land area of 1.75 Ha of Rp. 23.106.500 / mt, and the expenditure of farmers who have a land area of 2 Ha of Rp. 26.684.000 / mt. (3) The minimum land area that farmers must cultivate to fulfill their needs is 1 Ha.